Honest advocacy for nature: presenting a persuasive narrative for conservation - Rose, David; Brotherton, Peter; Owens, Susan; Pryke, Thomas (New Zealand Science Review, 2016)
​ Conservation scientists are increasingly recognising the value of communicating policy-relevant knowledge to policy-makers. Whilst considerable progress has been made in offering practical advice for scientists seeking to engage more closely with decision-makers, researchers have provided few tangible examples to learn from. This paper uses an English case study but draws out important high-level messages relevant to conservation scientists worldwide. The case study looks at how the Lawton Review presented knowledge persuasively about the suitability of England’s ecological network to deal with future pressures. Through skilful framing of rigorous scientific knowledge it was able to make a significant impact on government policy. Impact was achieved through: (1) selecting politically salient frames through which to communicate; (2) using clear, accessible language; and (3) conducting rigorous science using an authoritative team of experts. Although its publication coincided with a favourable policy window, the Lawton Review seized on this opportunity to communicate a rigorously argued, persuasive and practical conservation message; in other words, it performed ‘honest advocacy’. Thus, whilst it remains important to conduct scientific research with technical rigour, conservation scientists could also benefit from identifying salient frames for conservation and communicating clearly.